Friction and cohesion coefficients of composite concrete-to-concrete bond - Mohamad, Mazmira E. (Elsevier, 2015)
Experimental study is conducted to quantitatively assess the effects of different surface textures on the friction and cohesion coefficients of concrete-to-concrete bond under different normal stresses. The top surface of concrete base specimens are treated with five different surface textures; surface "left as-cast", deep groove, indented, and wire-brushing in longitudinal and transverse directions. The roughness profile of the treated concrete base is measured using a portable stylus roughness instrument. In addition, the "push-off" test method is conducted to determine the relationship between the roughness profile and the interface shear strength. Results show that the mean peak height, Rpm has the most significant influence on the pre-crack interface shear strength where the correlation coefficients, R2 ranged from 0.9009 to 0.9209. Analytical equations are then proposed to predict the friction and cohesion coefficients by integrating Rpm into the proposed equations. The comparison shows a good concordance with the experimental results within an acceptable range